Neuroameliorative effects of berry extracts in Alzheimer induced rats - FAROUK K. EL-BAZ,; HANAN F. ALY,; WAGDY K. B. KHALIL,; HODA F. BOOLES, (International Journal of Pharma and Bio Sciences, 2016)
This study was designed to evaluate the neuro-ameliorative effect of red (Morus rubra) and white berry (Morus alba) extracts against Alzheimer´s disease (AD) in male rats. AlCl3 was administered orally to male albino rats (100 mg/kg/day for 6 weeks) while, berry extracts (300 mg/kg/day for six weeks) was administered orally post AlCl3 administration. The data showed markedly elevation in lipid peroxide, apoptotic marker enzyme (caspase-8) and calmodulin (CaM) levels while, reduced glutathione (GSH) level and antioxidant enzyme paraoxanase-1 (PON1) were reduced in AD rats when compared with normal control one. The treatment of rats with AlCl3 induced AD was associated with increase in the 8-OHdG/2-dG ratio and decreased the expression of DHCR24 and FKBP1B genes. However, the treatment of AD-induced rats with red and white berry extracts exhibited low 8-OHdG/ 2-dG ratio and increase the expression of the DHCR24 and FKBP1B genes. The results suggested the attenuated role of berry extracts which could be attributed to the inhibition of reactive oxygen species (ROS), increase in the antioxidant enzymes activity as well as inhibition in the occurrence of apoptotic related enzymes such as caspases-8.